A comparison of three different notching ions for small-scale fracture toughness measurement. (February 2016) - Best, James P.; Zechner, Johannes; Shorubalko, Ivan; Oboňa, Jozef Vincenc; Wehrs, Juri; Morstein, Marcus; Michler, Johann
Abstract: While small-scale fracture toughness measurements provide an extremely useful material parameter, notch preparation and ion-beam damage continue to be contentious issues. Herein we utilize a conventional gallium source for notching ceramic cantilevers, and compare against notches fabricated using xenon and helium ions from commercial focused ion microscopes. This is the first time ions other than gallium have been used for notches in such measurements. We observe some statistical dependence of the measured toughness on the utilized notching ion, bringing into question the influence of ion-material interactions in creating residual stresses or embrittlement in the small volumes around the notch root. Graphical abstract: